Partnerships between philanthrocapitalists and donors: the case of Girl Hub. Issue 7 (3rd October 2021) - Shutt, Catherine Ann
ABSTRACT: Partnerships between traditional aid institutions and private sector actors have become an accepted feature of the international aid architecture. This paper explores the opportunities and challenges presented by such relationships through an analysis of Girl Hub, an operational partnership between Nike's philanthropic foundation and the United Kingdom's Department for International Development (DfID). Despite both parent organisations sharing a commitment to girl empowerment and economic development, Girl Hub failed to achieve its founders' vision. Ultimately, the influence of the philanthropic organisation was mediated by DfID's accountability demands and culture clashes between individuals involved in the partnership.